2018
DOI: 10.1093/ibd/izy013
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Puzzle of Nonadherence in IBD—Assembling the Pieces

Abstract: Nonmodifiable characteristics such as female sex and UC are associated with low adherence. Good communication with the treating physician and understanding the disease are modifiable factors associated with high adherence. Early intervention might improve patients' adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…Sense of coherence was already investigated among IBD patients [15] and was found to influence the development of anxiety and depression [15] regardless of disease severity. On the other hand, in our recently published study [23] of adherence in IBD patients, multivariate analysis did not find a significant difference in the SOC scores between adherent and non-adherent patients. These results, in addition to those of the current study, raise several questions.…”
Section: Discussioncontrasting
confidence: 73%
“…Sense of coherence was already investigated among IBD patients [15] and was found to influence the development of anxiety and depression [15] regardless of disease severity. On the other hand, in our recently published study [23] of adherence in IBD patients, multivariate analysis did not find a significant difference in the SOC scores between adherent and non-adherent patients. These results, in addition to those of the current study, raise several questions.…”
Section: Discussioncontrasting
confidence: 73%
“…A French study (Nahon and colleagues) reported that higher proportion of females were adherent to medication whereas Ediger et al and colleagues from Canada and another study from Israel reported higher rate of nonadherence in females. 24,27,28 Upto 10 more studies did not show any correlation between gender and adherence. 6 Lakatos, 29 reported low level of education was significantly associated with nonadherence (35.1%) compared with high education (13.8%) (P = 0.026).…”
Section: Discussionmentioning
confidence: 95%
“…UC was a risk factor for nonadherence in 2 studies whereas CD was associated with nonadherence in one study. 24,28,30 Left sided disease has been shown to associated with nonadherence whereas 4 other studies reported no association of disease extends and nonadherence. 6,26 Four studies reported that nonadherence is associated with shorter duration of disease 23,[31][32][33] whereas 1 study reported the contrary.…”
Section: Discussionmentioning
confidence: 98%
“…8 Others demonstrated that good communication with the physician and understanding the disease as predictors for high adherence. 9 Different tools such as patient questionnaire, patient diary, pharmacy refill data, interviews, physician perception, pill counters, drug levels and drug metabolites are used to identify and measure adherence. 10 In general, objective assessments of adherence are lower than subjective measurements.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Others demonstrated that good communication with the physician and understanding the disease as predictors for high adherence. 9 …”
Section: Introductionmentioning
confidence: 99%